Побудова формальної моделі наукової публікації - Проскудіна, Галина; Овдій, Ольга (Видавництво Львівської політехніки, 2012)
The paper concerns resource conceptual model creation for research and digital libraries information systems, particularly the publication model as one of main resources of a research environment. Also well-known connected projects are discussed such as ЕНИП, CERIF, SPAR, CIDOC CRM, FRBR.
Keywords: інформаційний ресурс; модель; наукова публікація; науковий простір; електронні бібліотеки